Germination of Quercus ilex and Q. pubescens in a Q. ilex coppice - Bran, D; Lobreaux, O; Maistre, M; Perret, P; Romane, F (Plant Ecology, 1990)
Quercus ilex L. (holm oak) coppices, widespread around the Mediterranean basin, are probably the result of 5 000 years of prolonged human disturbance of the original Quercus pubescens Willd. (downy oak) forests. Since disturbance has almost ceased in recent years, a question arises as to the development of these coppices: will the Q. pubescens forests return, or will Q. ilex remain the dominant species? To investigate the phenomenon, we analyzed the first stages, i.e. germination of the two species in holm oak coppices. Our experiments show that both species germinated better in coppices than in clearings or clear-cuts. Moreover, Q. pubescens appears to be slightly favored above Q. ilex and it is suggested auto-allelopathy is involved, at least partially inhibiting the germination of Q. ilex.
Keywords: dynamics; Mediterranean climate; Southern France; succession